Edukasi Gizi Pada Remaja di SMP Negeri 11 Pekanbaru Kecamatan Tenayan Raya Kota Pekanbaru : Edukasi Gizi Pada Remaja di SMP Negeri 11 Pekanbaru Kecamatan Tenayan Raya Kota Pekanbaru - Fitri; Restusari, Lily; Arsil, Yuliana (Jurnal Pengabdian Kesehatan Komunitas (Journal of Community Health Service), 2022)
Background During adolescence, physical, mental and emotional growth changes very rapidly. There needs to be nutritional education for adolescents about nutrition, nutritional status, anemia as well as increasing adolescent nutritional knowledge and improving the balance of their behavior so that it can influence habits in choosing healthy foods. Providing nutrition education through books is something that teenagers are interested in and likes. Objectives. Is to provide nutrition education to students at SMP Negeri 11 Pekanbaru, Tenayan Raya District, Pekanbaru City. Methods, education for teenagers in the form of counseling and educational media in the form of books. This activity was attended by 90 students of SMP Negeri 11 Pekanbaru City. Understanding of the material provided is about Nutrition (My Plate Contents, 4 Pillars of Balanced Nutrition, Principles of Balanced Nutrition), Nutritional Status, Physical Activity, Nutritional Problems in Adolescents (anemia, obesity, underweight/undernutrition and chronic energy deficiency/KEK). Measurement indicators use pre and post test questionnaires. Results. Pre-test score, good knowledge 3.33%, sufficient knowledge 67.77% and less knowledge 28.88%, after the post-test, good knowledge 21.11%, sufficient knowledge 63.33%, and less 15, 55%. Conclusion. Educational activities with the application of Balanced Nutrition for Healthy Adolescents are known to be 100% well-informed. Suggestion. The school is expected to continue providing nutrition education to teenagers. Students of SMPN 11 Pekanbaru use books or other media as an effort to suppress the occurrence of nutritional problems in adolescents. Abstrak Pada masa remaja pertumbuhan fisik, mental dan emosional berubah sangat cepat. Perlu adanya pendidikan gizi pada remaja tentang gizi seimbang, status gizi, anemia serta aktifitas fisik untuk meningkatkan pengetahuan gizi remaja dan mengubah sikap perilaku mereka sehingga dapat mempengaruhi kebiasaan dalam memilih makanan yang sehat. Pemberian edukasi gizi melalui buku merupakan hal yang diminati dan disukai remaja dapat menjadi pilihan. Kegiatan ini bertujuan untuk memberikan edukasi gizi pada siswa di SMP Negeri 11 Pekanbaru Kecamatan Tenayan Raya Kota Pekanbaru. Edukasi diberikan kepada remaja berupa penyuluhan dengan media edukasi berupa buku. Kegiatan ini diikuti oleh siswa dan siswi SMP Negeri 11 Kota Pekanbaru sebanyak 90 orang. Pemahaman materi yang diberikan mengenai Gizi seimbang (Isi Piringku, 4 pilar Gizi Seimbang, Prinsip gizi seimbang), Status Gizi, Aktifitas Fisik, Permasalahan gizi pada remaja (anemia, obesitas, underweight/gizi kurang dan Kurang energi kronik/KEK). Indikator pengukuran menggunakan kuisioner pre dan post-test. Nilai pre-test, pengetahuan baik 3,33 %, pengetahuan cukup 67,77 % dan pengetahuan kurang 28,88 %, setelah dilakukan post – test, pengetahuan baik 21,11 %, pengetahuan cukup 63,33%, dan pengetahuan kurang 15,55 %. Kegiatan edukasi dengan penerapan buku Gizi Seimbang untuk Remaja Sehat diketahui sebanyak 100 % berpengetahuan baik. Saran. Pihak sekolah diharapkan dapat melanjutkan pemberian edukasi gizi kepada remaja Siswa/I SMPN 11 Pekanbaru menggunakan buku atau media lain sebagai salah satu upaya menekan terjadinya permasalahan gizi pada remaja.